Epididymitis, orchitis, and epididymo-orchitis associated with SARS-CoV-2 infection in pediatric patients: A systematic review - Inouye, Daniel; Baker, Zoë; Peña, Adam; Vasquez, Evalynn (Frontiers in Urology, 2023)
Introduction: Epididymitis, orchitis, and epididymo-orchitis (EO) are common disorders in pediatric patients which may be caused by infection, trauma, or inflammation. SARS-CoV-2 associated EO has been previously described, particularly in adults. However, no systematic reviews of these manifestations in pediatric patients yet exist. We present a systematic literature review of epididymitis, orchitis, and EO associated with SARS-CoV-2 in pediatric patients to shed light on these relatively rare, yet potentially severe, conditions to understand presentation, course of illness, management options, and outcomes. Materials and Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic review was performed using specified key terms to search PubMed, Cumulative Index to Nursing and Allied Health Literature, Web of Science, and Embase. Articles were independently screened by two reviewers. Manuscripts with detailed descriptions of SARS-CoV-2 associated epididymitis, orchitis, or EO in pediatric patients were included. Exclusion criteria included: no clear diagnosis of the target diseases and no detailed clinical course described. Quality and bias were assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Case Reports. Results: 60 records were initially identified, with 6 case reports included in the systematic review. All 6 patients included presented with fever and genitourinary symptoms. Four patients were also diagnosed with multisystem inflammatory syndrome in children (MIS-C). One patient underwent surgical exploration for presumed testicular torsion, though intraoperatively there was no evidence of torsion. All patients recovered without documented long-term sequelae. Discussion: While observational studies are prone to bias, this systematic review suggests that epididymitis, orchitis, and EO are significant manifestations of SARS-CoV-2 that may mimic urologic emergencies (i.e., testicular torsion). Providers should suspect these conditions in pediatric COVID-19 patients with scrotal symptoms, particularly with associated MIS-C. The long-term genitourinary sequelae of SARS-CoV-2 should be investigated, including the effects on pediatric patients undergoing reproductive development.